Attribute-based proxy re-encryption scheme with multiple features - Chaosheng FENG; Wangping LUO; Zhiguang QIN; Ding YUAN; Liping ZOU (Tongxin xuebao)
A ideal proxy re-encryption scheme has five features,such as one-way encryption,non-interaction,repeatability,controllability and verifiability.The existing schemes,however,have only two or three of the five features,which reduces the utility of them to some extent.For this,a new ciphertext-policy attribute-based proxy re-encryption (CP-ABPRE) scheme with the above five features was proposed.In the proposed scheme,the cloud proxy server could only re-encrypt the ciphertext specified by the delegator by using the re-encryption key,and resist the collusion attack between the user and the proxy satisfying the re-encryption sharing policy.Most of encryption and decryption were outsourced to cloud servers so that it reduced the computing burden on the user’s client.The security analysis show that the proposed scheme resists the selective chosen plaintext attack (SCPA).